Girl in the red dress TANGO - Gordey, Gordon (My University, 2014)
Gordon Gordey documents his dance concepts and libretto, including performance photographs, for the creation of the original dance theatre work Girl in the Red Dress TANGO. Created for the Ukrainian Shumka Dancers of Canada.
Keywords: tango; Ukrainian Shumka Dancers; Ukrainian dance; folk dance; Canadian dance; multiculturalism; Yaroslav Barnych; Bohdan Veselovsky; ethnic dance; Dave Ganert; Leo Sato; Andrij Shoost